Efficacy of a Non-addictive Nasal Irrigation Based on Sea Salt Enriched with Natural Enzymes among Patients with Sinusitis: An In Vivo, Randomized, Controlled Trial - Nocini, Riccardo; Di Cosola , Michele; Cazzolla, Angela Pia; Cantore, Stefania; Castellaneta, Francesca; Covelli , Michele (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Chronic rhinosinusitis (CRS) is a common condition that is defined as inflammation of the nose and paranasal sinuses. Nasal irrigation plays an important role in the treatment of CRS. Evidence from basic research favors hypertonic saline over isotonic saline for mucociliary clearance, but evidence from clinical studies is controversial. AIM: This study aims to investigate the hypothesis that the use of daily nasal irrigation based on sea salt, enriched with natural enzymes and lysozyme, may be useful in patients with CRS. PATIENT AND METHODS: Patients (30 men and 30 women) 18–55 years old (mean age 41 ± 3 y.o.), with two episodes of acute sinusitis or one episode of chronic sinusitis per year for 2 consecutive years, were enrolled stratified by sex and age and randomly divided into two groups supplementation: Group A (test) and Group B (control/placebo). Moreover, an exit questionnaire was asked to Group A subjects to report whether their sinus-related quality of life has gotten worse, stayed the same, or improved (scale from 0 to ±100%). RESULTS: The result showed that in the test group (A) from T0 to T1, a reduction of 17.65% for the symptoms related headache and/or facial pressure and a reduction of the 18.18%, for the symptoms relates to congestion and/or nasal discharge. On the other hand, the control group (B) shown less difference between T0 and T1. CONCLUSIONS: This study strengthens the argument that the tested formulation is a safe, well-tolerated, long-term therapy that patients with chronic sinonasal complaints can and will use at home with minimal training and follow-up.